Preparation method and application of cobalt-doped nano-tungstic acid catalyst
By anchoring Co2+ on the nanotungstate support, a cobalt-doped nanotungstate catalyst was prepared, which solved the problem that the prior art was difficult to remove organic dye pollutants in wastewater, and achieved efficient dye degradation effect.
Patent Information
- Application Number
- CN202410772188.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-06-17
AI Technical Summary
The prior art is difficult to effectively remove organic dye pollutants in wastewater, especially new carmine, which are harmful to human health.
Nanotungstenic acid with a unique hollow spherical structure was synthesized by the self-template method and anchored Co2+ as a catalyst support to prepare a cobalt-doped nanotungstenic acid catalyst (Co/H2WO4) for degrading organic dyes with the PMS system.
The catalyst achieved 100% degradation of new carmine within 40 minutes, exhibited efficient degradation performance, and had strong resistance to inorganic ions and pH values.
Smart Images

Figure CN118751252B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts and relates to a preparation method of a cobalt-doped nano-tungstic acid catalyst and application of the catalyst in organic dye degradation. Background Art
[0002] Due to increasingly stringent regulations and increasing public environmental awareness, there is an urgent need to develop effective technologies to remove organic dye pollutants from wastewater. For example, new carmine (NC) is an artificial red azo compound that is commonly used in the food and beverage industry due to its low cost and high stability. However, long-term or large-scale ingestion of NC is harmful to human health because it can produce mutagenic precursors (aromatic amines) that cause serious diseases such as cancer. Currently, several methods have been developed to purify wastewater contaminated with organic dyes, such as adsorption technology, membrane filtration, biodegradation, photocatalytic degradation, chemical oxidation, and electrochemical oxidation.
[0003] In recent years, advanced oxidation processes (AOPs) have been widely used for refractory and emerging pollutants as a promising approach to achieve complete mineralization of most organic pollutants. 2 O 2 Widely used for the oxidation of organic pollutants due to its stability and ease of handling, this highly reactive oxidant is also used in the biochemical and polymer industries to provide reaction-initiating free radicals. Compared with the traditional Fenton process, PMS has the advantages of higher redox potential, longer free radical half-life and wider pH range for water purification.
[0004] Tungsten trioxide (WO 3 ) and its hydrates are very important multifunctional new materials with octahedral segments of oxygen around the W atom. Tungsten trioxide is usually obtained by the pyrolysis process of its hydrate. As a transition metal oxide, it is an n-type semiconductor material with excellent electrochromic and photochromic properties, as well as good catalytic properties. Therefore, they are widely used in photocatalysis and light-assisted PMS systems. At the same time, in order to meet its application, nano-microspheres of various shapes, such as prismatic, nano-sheets, nano-rods and nano-flower microspheres, have been developed. It can be used not only directly as a catalyst, but also as a catalyst carrier with synergistic effects. Especially for tungstic acid, it is more accessible and has abundant surface oxygen-containing functional groups as basic sites for anchoring transition metal ions. Surprisingly, researchers have paid little attention to tungstic acid-based materials as catalyst supports in PMS activation and degradation reactions.
[0005] Since tungstic acid is widely used in catalysts, dyes, cosolvents and aerospace materials, the industry needs to prepare a large amount of high-purity tungstic acid. Generally, tungstic acid is made of sodium tungstate as the main raw material, with a certain amount of nitric acid and hydrochloric acid added. The resulting product is often colloidal and difficult to wash and filter.
[0006] In the prior art, the preparation processes of tungstic acid include: acid decomposition of scheelite concentrate, acid decomposition of tungsten concentrate after alkali leaching, sodium tungstate method, artificial scheelite method, sodium ammonium paratungstate method and ammonium paratungstate (APT) method, etc. The purity and properties of tungstic acid prepared by the above methods are different, and because the amount of tungsten salt and concentrate that can be dissolved in water is small, it is difficult for the two to react completely. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing a cobalt-doped nano-tungstic acid catalyst and its application, and synthesizes nano-tungstic acid (H2O4) with a unique hollow sphere structure by a self-template method. 2 WO 4 ), the prepared nano-tungstic acid was used as a catalyst carrier to anchor Co 2+ , and obtain the cobalt-doped nanotungstate catalyst (Co / H 2 WO 4 ), applied to the degradation of organic dyes.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing a cobalt-doped nano-tungstic acid catalyst, comprising the following steps:
[0010] S1, heating the hydrochloric acid solution, then adding a predetermined proportion of tungsten source, stirring and reacting to obtain a tungstic acid solution;
[0011] S2, adding a set proportion of oxidant to the tungstic acid solution obtained in step S1, reacting at a predetermined temperature to dissolve the oxidant into nano-peroxytungstic acid;
[0012] S3, adding hydrochloric acid solution to the nano-peroxytungstic acid solution obtained in step S2, and further hydrolyzing to obtain nano-tungstic acid;
[0013] S4, filtering, washing, and drying the nano-tungstic acid obtained in step S3 to obtain a nano-tungstic acid product;
[0014] S5, adding the nano tungstic acid product obtained in step S4 into the solution containing the cobalt source, stirring sufficiently, washing the precipitate, and drying to obtain the cobalt-doped nano tungstic acid catalyst.
[0015] In a preferred embodiment, the tungsten source is selected from ammonium paratungstate, ammonium metatungstate, or a combination of the two;
[0016] The oxidant is hydrogen peroxide;
[0017] The cobalt source is selected from one or more combinations of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate and cobalt oxalate.
[0018] In a preferred embodiment, in step S1, the molar ratio of hydrochloric acid to tungsten source is 1 to 3:1; the tungsten source is preferably ammonium paratungstate (ATP).
[0019] In a preferred embodiment, in step S1, the reaction temperature is 40 to 80° C., and the reaction time is 10 to 60 minutes.
[0020] In a preferred embodiment, in step S2, the molar ratio of hydrogen peroxide to tungstic acid is 1 to 10:1.
[0021] In a preferred embodiment, in step S2, the reaction temperature is 50-80° C., and the reaction time is 5 min-120 min.
[0022] In a preferred embodiment, in step S3, the molar ratio of hydrochloric acid to peroxytungstic acid is 1 to 10:1.
[0023] In a preferred solution, in step S4, the nano-tungstic acid is washed with water for multiple times until the washing precipitate has a pH value of 4-6.
[0024] In a preferred embodiment, in step S4, the drying temperature is 40 to 60° C. and the drying time is 12 to 48 hours.
[0025] In a preferred solution, in step S5, the doping amount of the cobalt source is 0.1-10% of the nano-tungstic acid product.
[0026] In a preferred embodiment, in step S5, washing is performed with deionized water, and then drying is performed at 30 to 50° C. for 6 to 24 hours.
[0027] The invention also provides application of the cobalt-doped nano-tungstate catalyst in degradation of organic dyes.
[0028] Principle of the present invention: Transition metal ions, such as Fe 2+ , Cu 2+ , Mn 2+ and Co 2+ Coupling with PMS can accelerate the generation of reactive oxygen species (ROS), thereby improving oxidation efficiency. ROS include free radicals and non-free radicals, such as sulfate (SO4· - ), hydroxyl group (·OH), superoxide (O 2 · - ) and singlet oxygen ( 1 O 2 ). Singlet oxygen ( 1 O 2) as a non-radical oxidizing species, exhibits significant advantages in half-life, oxidant utilization efficiency and selective oxidation of organic matter. 1 O 2 The pathway dominated by Co has been successfully demonstrated to have good resistance to common water matrices. 2+ have been identified as the most effective species for PMS activation. However, the difficulty in recovering them from homogeneous systems and the highly toxic Co 2+ The leaching of cobalt hinders their practical application. To overcome this shortcoming, heterogeneous cobalt-based catalysts have been widely developed as one of the potential water treatment methods. The selection of cobalt carriers is also very critical for obtaining high-performance catalysts. In wastewater treatment, the addition of carriers can improve the catalytic performance of cobalt due to the synergistic effect of multiple active sites on redox reactions. Therefore, the addition of Co 2+ Anchored in nanotungstate (H 2 WO 4 ) carrier is the key to its successful application.
[0029] The beneficial technical effects of the present invention are:
[0030] (1) The present invention has successfully explored a method and conditions suitable for preparing nano-tungstic acid, and the prepared tungstic acid nanosheets are self-assembled into a hollow sphere structure. The present invention dissolves a tungsten source in water, adds excess hydrochloric acid, and fully hydrolyzes the tungsten source to obtain large-particle tungstic acid, then dissolves the large-particle tungstic acid with hydrogen peroxide to obtain dissolved or partially dissolved tungsten peroxide, and finally adds hydrochloric acid to dissolve or partially dissolve the peroxytungstic acid, and finally hydrolyzes to obtain high-purity, nano-scale tungstic acid H 2 WO 4 The prepared nano-tungstic acid was used as a catalyst carrier to anchor Co 2+ , and obtain the cobalt-doped nanotungstate catalyst (Co / H 2 WO 4 ).
[0031] (2) Since cobalt ions have strong coordination with the abundant oxygen-containing functional groups in tungstate, Co / H 2 WO 4 catalyst and used it for PMS. Due to the unique staggered nanosheet shell with hollow interior and H 2 WO 4 Due to the synergistic effect of the support and the Co active component, the composite exhibited attractive degradation performance, achieving 100% degradation of neocarmine (NC) within 40 min.
[0032] (3) The interconnected nanosheets and the hollow interior cavity can not only 2+The loading provides a large surface area and helps to significantly improve the reaction contact efficiency during the degradation process. Studies have found that the generated hydroxyl radicals (·OH) and superoxide (O 2 · - ) compared to singlet oxygen ( 1 O 2 ) are the main reactive oxygen species that play a key role in the efficient degradation of NC.
[0033] (4)Co / H 2 WO 4 The / PMS system also showed strong resistance to inorganic ions and pH values during degradation. This work not only provides a basis for the design of H 2 WO 4 This provides a new and effective strategy and a reference for designing high-performance catalysts in water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the preparation process and working principle diagram of cobalt-doped nano-tungstic acid catalyst.
[0035] Figure 2 This is the SEM image of nano-tungstic acid prepared in Example 1.
[0036] Figure 3 This is a local enlarged view of the nano-tungstic acid prepared in Example 1.
[0037] Figure 4 The Co / H prepared in Example 1 2 WO 4 SEM image of .
[0038] Figure 5 The Co / H prepared in Example 1 2 WO 4 A partial enlarged view of .
[0039] Figure 6 The Co / H prepared in Example 1 2 WO 4 TEM images and mapping images.
[0040] Figure 7 Nano-tungstic acid, Co / H prepared in Example 1 2 WO 4 XRD pattern of .
[0041] Figure 8 Nano-tungstic acid, Co / H prepared in Example 1 2 WO 4 XPS graph.
[0042] Fig. 9The Co / H prepared in Example 1 2 WO 4 Catalytic performance analysis diagram.
[0043] Fig.10 Fe / H prepared in Comparative Example 1-2 2 WO 4 and Cu / H 2 WO 4 Catalytic performance analysis diagram.
[0044] Fig.11 The Co / H prepared in Example 1 2 WO 4 Catalytic degradation stability analysis diagram. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] Unless otherwise specified in this embodiment, the reagents used are all common commercial products or prepared by conventional means, and the equipment used are all conventional equipment in the art. The following are some embodiments of the inventor's experiments:
[0047] Example 1
[0048] A method for preparing a cobalt-doped nano-tungstic acid catalyst comprises the following steps:
[0049] 1) Take hydrochloric acid and APT in a molar ratio of 2:1, heat the hydrochloric acid solution to 60°C, add 3g of ammonium paratungstate powder (0.001mol) at one time, heat the hydrochloric acid solution to 50°C, add the ammonium paratungstate powder at one time, and react for 0.5 hours by magnetic stirring to obtain tungstic acid;
[0050] 2) Add 10 ml of hydrogen peroxide (30% concentration) to the above solution, and stir under magnetic force at 60° C. for 30 minutes to dissolve it into nano-peroxytungstic acid;
[0051] 3) Prepare 50 ml of 0.090 mol hydrochloric acid solution, add it into the above nano peroxytungstic acid solution, and further hydrolyze it into nano tungstic acid;
[0052] 4) Filter, wash with water for several times (wash the precipitate until the pH of the washing water is 4-6), and dry the sample at 40-60°C to obtain nano-tungstic acid;
[0053] 5) Add 2g of nano-tungstic acid product to 100ml of Co(NO 3 ) 2 6H 2 O (concentration of 0.5 mol / L) solution, fully stirred at room temperature for 2 h, washed the precipitate, and dried at 40 °C for 12 h to obtain Co / H 2 WO 4 catalyst, Figure 1 This is the preparation process and working principle diagram of cobalt-doped nano-tungstic acid catalyst.
[0054] Depend on Figures 2-3 It can be seen that the tungstate nanosheets prepared by the present invention are self-assembled into a hollow sphere structure with an average particle size D 50 The particle size of the tungstate nanosheet is about 1-2 um, the size of the tungstate nanosheet is about 200 nm, and the thickness of the tungstate nanosheet is about 20 nm.
[0055] Depend on Figures 4 to 6 Know Co 2+ The load on H 2 WO 4 The unique structure of H 2 WO 4 The H 2 WO 4 The nanosheets are interconnected to form many cavities between the nanosheets. These cavities, the interlaced 2D nanosheet surfaces, and the hollow structures inside them can not only provide a large area for Co loading and adsorption / reaction sites in the PMS activation reaction, but also contribute to the effective mass diffusion in the degradation process, significantly improving the catalytic degradation performance of pollutants.
[0056] Depend on Figure 7 It can be seen that the characteristic peaks of the nano-tungstic acid prepared in the present invention at 2θ=16.53°, 25.38°, 56.15°, 38.88°, 49.68°, 52.77° and 56.15° belong to H 2 WO 4 (JCPDS card number 84-0886) on the crystal planes (020), (111), (131), (022), (202), (222) and (311), there are no Co-related crystallization peaks and characteristic peaks of other substances, and the peaks are strong and narrow, indicating that the product is relatively pure and has good crystallinity. 2 WO 4 The XRD results of the catalyst show that the cobalt loading has no effect on the crystal phase of tungstic acid.
[0057] Depend on Figure 8It can be seen that the XPS results of nano-tungstic acid show that the fitted W fine spectrum presents a typical two-peak structure, with binding energies at 35.70 and 37.92 eV for hexavalent W. In addition to hexavalent W, a small amount of characteristic peaks belonging to pentavalent W are found at binding energies of 34.66 and 36.39 eV. This shows that the prepared nano-tungstic acid is mainly hexavalent, with a small amount of pentavalent. 2 WO 4 XPS of the catalyst shows that after adding Co, the characteristic peak of the OH group shifts significantly to form a Co-OH group, indicating that some Co elements have strong chemical interactions with the tungstic acid carrier, which is beneficial to the loading and anchoring of the active components of the catalyst and improves the stability of the catalyst during recycling.
[0058] Comparative Example 1
[0059] The process parameters of this embodiment are the same as those of embodiment 1, except that the nano-tungstic acid product is added to the Fe(NO 3 ) 3 9H 2 O solution, Fe / H 2 WO 4 catalyst.
[0060] Comparative Example 2
[0061] The process parameters of this embodiment are the same as those of embodiment 1, except that the nano-tungstic acid product is added to the Cu(NO 3 ) 2 6H 2 O solution to obtain Cu / H 2 WO 4 catalyst.
[0062] Test Case
[0063] 50 ml of new carmine (NC) (20 mg·L -1 ) solution was placed in a 100 ml beaker, and 25 mg of the catalyst prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was added. The solution was then dispersed for 30 minutes by ultrasonic treatment in the dark until adsorption equilibrium was reached. Subsequently, a certain amount of PMS was added to the NC solution for degradation experiments. In addition, before adding the catalyst, the initial pH of the solution was adjusted with 0.1 M HCl or NaOH solution. At the same time, the degradation of the NC solution was measured at each time interval.
[0064] The test results are as follows:
[0065] like Fig. 9 The test results shown show that Co / H 2 WO 4The catalyst has excellent catalytic activation effect on PMS and shows high removal efficiency in the degradation process of carmine dye, with the degradation rate approaching 100% after 40 minutes.
[0066] like Fig.10 Shown is a comparative analysis of catalysts prepared by Fe and Cu active components. The results show that Cu has almost no degradation ability for PMS activated catalytic degradation of carmine dye, and although the Fe component can play a role in PMS activation catalysis, its degradation performance is much lower than that of the Co component.
[0067] Fig.11 The Co / H prepared in Example 1 2 WO 4 The catalytic degradation stability analysis chart shows that Co / H 2 WO 4 The catalyst has excellent cyclic stability.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of implementation of the present invention. If the present invention is modified or replaced by equivalents without departing from the spirit and scope of the present invention, it should be included in the protection scope of the claims of the present invention.
Claims
1. Application of a cobalt-doped nano-tungstic acid catalyst in the degradation of organic dyes, characterized in that ; The preparation method of the cobalt-doped nano-tungstic acid catalyst comprises the following steps: S1, heating the hydrochloric acid solution, then adding a predetermined proportion of tungsten source, stirring and reacting to obtain a tungstic acid solution; S2, adding a set proportion of oxidant to the tungstic acid solution obtained in step S1, reacting at a predetermined temperature to dissolve the oxidant into nano-peroxytungstic acid; S3, adding hydrochloric acid solution to the nano-peroxytungstic acid solution obtained in step S2, and further hydrolyzing to obtain nano-tungstic acid; S4, filtering, washing, and drying the nano-tungstic acid obtained in step S3 to obtain a nano-tungstic acid product; S5, adding the nano-tungstic acid product obtained in step S4 to the solution containing the cobalt source, stirring sufficiently, washing the precipitate, and drying to obtain the cobalt-doped nano-tungstic acid catalyst; The tungsten source is selected from one or a combination of ammonium paratungstate and ammonium metatungstate; The oxidant is hydrogen peroxide; The cobalt source is selected from one or more combinations of cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate and cobalt oxalate; In step S2, the molar ratio of hydrogen peroxide to tungstic acid is 1-10:1; In step S3, the molar ratio of hydrochloric acid to peroxytungstic acid is 1-10:
1.
2. The use of the cobalt-doped nano-tungstic acid catalyst in the degradation of organic dyes according to claim 1, characterized in that: In step S1, the molar ratio of hydrochloric acid to tungsten source is 1-3:
1.
3. The use of the cobalt-doped nano-tungstic acid catalyst in the degradation of organic dyes according to claim 1, characterized in that: In step S1, the reaction temperature is 40-80°C, and the reaction time is 10 min-60 min.
4. The use of the cobalt-doped nano-tungstic acid catalyst in the degradation of organic dyes according to claim 1, characterized in that: In step S2, the reaction temperature is 50-80°C, and the reaction time is 5 min-120 min.
5. The use of the cobalt-doped nano-tungstic acid catalyst in the degradation of organic dyes according to claim 1, characterized in that: In step S4, the nano-tungstic acid is washed with water for multiple times until the washing precipitate has a pH value of 4-6.
6. The use of the cobalt-doped nano-tungstic acid catalyst in the degradation of organic dyes according to claim 1, characterized in that: In step S5, the doping amount of the cobalt source is 0.1-10% of the nano-tungstic acid product.
Citation Information
Patent Citations
Preparation method and application of WO3 nano array photocatalyst rich in oxygen vacancies
CN114225944A
KR1018008110000B1